2012
DOI: 10.1177/1538574411418843
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous Loop Grafts for Free Tissue Transfer

Abstract: Arteriovenous (AV) loop grafts are a type of vascular conduit that can be used to support free tissue transfer. Wounds of various etiologies may require free tissue transfer, and the AV loop graft is a useful adjunct when adjacent blood supply is inadequate. Here we present 2 cases and review the technique and published literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…The two‐stage approach, however, creates two manageable and controlled operations, which can be beneficial in hostile tissue environments or in complex wounds or patients. This approach also ensures that there are never more than two new anastomoses to investigate in case of free flap compromise (Lind et al, ). In a two‐stage reconstruction, arterialization of the vein theoretically allows for reduced resistance to venous outflow at time of flap transfer which could decrease venous stasis and, potentially, thrombus formation (Sorensen et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two‐stage approach, however, creates two manageable and controlled operations, which can be beneficial in hostile tissue environments or in complex wounds or patients. This approach also ensures that there are never more than two new anastomoses to investigate in case of free flap compromise (Lind et al, ). In a two‐stage reconstruction, arterialization of the vein theoretically allows for reduced resistance to venous outflow at time of flap transfer which could decrease venous stasis and, potentially, thrombus formation (Sorensen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Literature review revealed 35 unique papers (Angel et al, 1993;Atiyeh & Musharafieh, 1997;Bruner, Jester, Sauerbier, & Germann, 2004;Cavadas, 2008;Demiri et al, 2009;Depprich, Naujoks, Meyer, Kubler, & Handschel, 2008;Devansh, 1995;Earle, Feng, & Jordan, 1990;Engel, Pelzer, Sauerbier, Germann, & Heitmann, 2007;Ethunandan, Cole, & Flood, 2007;Freedman, & Meland, 1989;Grenga & Yetman, 1987;Hallock, 1988Hallock, , 2012Karanas, Yim, Johannet, Hui, & Lineaweaver, 1998;Kim & Chandrasekhar, 1998;Lin & Butler, 2010;Lin et al, 2004;Lind, McCarthy, Derman, Jacobs, 2012;Moubayed et al, 2015;Mulholland et al, 1993;Oswald et al, 2007;Picard, Tiguemounine, Laure, Chabut, & Goga, 2004;Rand & Gruss, 1994;Rechnic, Edelson, & Fosburg, 1997;Reichenberger et al, 2010;Ritter et al, 1996;Silveira & Patricio, 1993;Sorensen, Muchardt, & Reumert, 1990;Sunar, Aygit, Afsar, Halici, & Duran, 2004;Tan, Cinal, Algan, & Barin, 2015;Threlfall et al, 1982;Vlastou & Earle, 1988;Vlastou, Earle, & Jordan, 1992;Wong, Lin, Fu, & Fang, 2009), which discussed utilizing AV loops in a single-stage approach and twelve papers which discussed utilizing AV loops in a two-stage approach for m...…”
Section: Meta-analysis Literature Reviewmentioning
confidence: 99%
“…Lengthening with additional microanastomosis is a classical procedure. Vein grafting is also a conventional and useful technique (Flores, Rad, Shridharani, Stapleton, & Rosson, ; Karanas, Yim, Johannet, Hui, & Lineaweaver, ), and the vascular loop technique (Jandali, Diluna, Storm, & Low, ; Lind, McCarthy, Derman, & Jacobs, ) and arteriovenous interposition grafting (Echo & Bullocks, ; Zenn, Pribaz, & Walsh, ) is a modification of conventional vein grafting. Other new procedures are based on using the natural vascular branching pattern of the subscapular vascular tree (Usami, Okazaki, Tanaka, Homma, & Yano, ) or branches of the ALT flap (Huang, Hsieh, Lai, Lin, & Chang, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the pedicle would not reach an anastomosis outside of the radiation field. A temporary arteriovenous loop was created in the neck with a saphenous vein graft and used to lengthen the pedicle of the latissimus flap [6, 7]. This allowed for a proper inset and ultimate healing of a chronically debilitating wound.…”
Section: Commentmentioning
confidence: 99%